2009
DOI: 10.1080/09593330903052830
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of endocrine disrupting compounds in water sources of Belo Horizonte Metropolitan Area, Brazil

Abstract: Endocrine disrupting compounds (EDCs) have attracted the attention of the scientific community because of the effects of EDCs on aquatic fauna and the potential threat they pose to human health. There are a handful of papers on the monitoring of EDCs in Brazilian surface waters, hence this research was aimed at assessing, by using liquid chromatography coupled to mass spectrometry (LC-MS), the presence of 17 beta-estradiol, 17 alpha-ethynylestradiol and 4-nonylphenol in surface waters used for supplying the Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 40 publications
1
21
0
17
Order By: Relevance
“…These values are also higher than those reported in other Brazilian regions. For example, in Minas Gerais, the average concentration of 17α-ethinylestradiol in waters nearby the capital, Belo Horizonte, is 206 ng/L, considering 15 positive data (34 % of the total) 46,47 . In the region of São Carlos (São Paulo), Campanha et al 39 reported an average value of 2 ng/L for 17β-estradiol in 24 positive data out of a total of 81 (30 %).…”
Section: Resultsmentioning
confidence: 99%
“…These values are also higher than those reported in other Brazilian regions. For example, in Minas Gerais, the average concentration of 17α-ethinylestradiol in waters nearby the capital, Belo Horizonte, is 206 ng/L, considering 15 positive data (34 % of the total) 46,47 . In the region of São Carlos (São Paulo), Campanha et al 39 reported an average value of 2 ng/L for 17β-estradiol in 24 positive data out of a total of 81 (30 %).…”
Section: Resultsmentioning
confidence: 99%
“…Após esses trabalhos, outros mais recentes, como Sodré et al (2007), Moreira et al (2009), Sodré et al (2010b, Moreira et al (2011) É comprovado que tanto os fármacos quanto os desreguladores endócrinos podem acarretar diversos efeitos prejudiciais à fauna aquá-tica, podendo propiciar diversos danos morfológicos, metabólicos e até alterações sexuais (BERGMAN et al, 2012;SANTOS, 2011). Dentre tais alterações, estão relatados: efeitos e danos na produção de esperma e feminização de machos; declínio na capacidade de reprodução; e até a ocorrência de óbitos e danos a descendentes (ROBINSON et al, 2003;Panter;THOMPSON;SUMPTER, 2000).…”
Section: De Acordo Com a Agência De Proteção Ambiental Dos Estados Ununclassified
“…É crescente o número de publicações internacionais que têm como objetivo investigar a presença de disruptores endócrinos associados a atividades industriais, e que são foco deste estudo -ftalatos, alquifenóis, bisfenol A e HPAs, em amostras ambientais aquosas, como águas superficiais, de abastecimento e subterrâneas, águas marinhas e efluentes (Azevedo et al, 2001;Liu et al, 2004;Serôdio e Nogueira, 2006;Gibson et al, 2007;Rezaee et al, 2009;Sánchez-Avila et al, 2009). No Brasil, os estudos conduzidos sobre disruptores sintéticos datam do início da década, sendo que grande parte foram desenvolvidos na região sudeste do país (Loureiro, 2002;Leandro, 2006;Ghiselli, 2006;Raimundo, 2007;Gerolin 2008;Moreira et al, 2009;Sodré et al, 2010 (Gruben et al, 2002).…”
Section: Dissertação De Mestrado Introduçãounclassified
“…Ferreira, 2007;Brasil, 2005a;Brasil, 2005b). (Loureiro, 2002;Leandro, 2006;Ghiselli, 2006;Raimundo, 2007; Gerolin 2008;Moreira et al, 2009;Sodré et al, 2010 (FIG. 1a).…”
Section: Introductionmentioning
confidence: 99%